Hubungan Pengetahuan Dengan Kejadian Dekompresi Pada Nelayan Tradisional Di Dusun Mamokeng Desa Tulehu Kecamatan Salahutu Kabupaten Maluku Tengah - Ernawati Hatuwe; Mirdat Hitiyaut; Hasna Tunny (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Background : decompression sickness is a disorder or disease that causes the cessation and increase of gas bubbles from the dissolved phase in the blood or tissues due to a decrease in pressure.this disease is still rare for the general public,but this is a special concern for divers. Objective : to determine the relationship of knowledge with decompression events in traditional fishermen in Mamokeng hamlet. Method : the research design used is a descriptive research design with a cross sectional approach with a sample income of 30 fishermen who live in Mamokeng Hamlet Tulehu Village Salahutu District Central Maluku Regency.sampling technique with total sampling technique.research instrument is a questionnaire.data processing using SPSS 16 data. Results : shows that there is a relationship between knowledge and decompression events in traditional fishermen using the person chi-square test with a value of p=0,001 (p=0,05) means that there is a significant relationship between decompression sickness and the knowledge of fishermen in the Mamokeng sub village.there is a relationship between knowledge and decompression events in Mamokeng Hamlet Tulehu Village Salahutu District Central Maluku Regency.